Effect of brief reflective parenting in parents of young children with autism spectrum disorder: Pre and post-intervention study - Saatvika Parashar; Sneha Das; Neha Sharma; Sonia Puar (Industrial Psychiatry Journal)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by marked impairments in social interaction and communication accompanied by a pattern of repetitive, stereotyped behaviors and activities. The prevalence rate after COVID-19 is 0.3%. Inferential processing style in parents plays a major role in maintaining the psychopathology in children. Brief reflective parenting intervention has not yet been studied in the context of inferential processing style in parents of young children with ASD. Aim: To study the effect of brief reflective training on parents of children with Autism spectrum disorder. Materials and Methods: This intervention study was conducted on parents of individuals diagnosed with ASD based on ICD-10 DCR, following certain inclusion and exclusion criteria. Data was collected from various General Hospital Psychiatry Unit in Delhi NCR, using a purposive sampling technique. Cognitive Style Questionnaire-Short Form was administered as an outcome measure to assess inferential negative style. Data was statistically analyzed using the Wilcoxon rank test. Results: Findings suggested improvement in inferential negative style after parents attended the intervention of brief reflective training workshop, and the improvement was statistically significant. Conclusion: The study highlights the potential benefits of brief reflective training in enhancing cognitive processing styles among parents of children with ASD.